Influence of Ca and Mg doping on the microstructure and optical properties of YAG ceramics - Chaika, M.A.; Vovk, O.M.; Doroshenko, A.G.; Klochkov, V.K.; Mateychenko, P.V.; Parkhomenko, S.V.; Fedorov, O.G. (Functional Materials, 2017)
Ceramics of yttrium aluminum garnet doped with Ca or Mg are produced by solid state reaction under vacuum sintering. The influence of CaO and MgO additives themselves on microstructure and optical properties of YAG ceramics is investigated. Ceramics of Mg-doped YAG is transparent while ceramics of Ca-doped YAG is fully opaque due to high concentration of residual porosity into later. Changing concentration of Ca affects significantly on the grain growth, the average grain size increase with increasing of Ca concentration. Changing concentration of Mg from 0.05 to 0.5 at.% doesn't influence on grain size of the ceramics. It is proposed that liquid appears on the grain boundaries of the ceramics due to CaO additive. This liquid causes increasing the diffusion of components through the grain boundaries that speed up the grain growth and traps the pores while no such liquid exists for MgO additive. This difference is determined by the different ways of interaction of CaO and MgO with the basic YAG components Al₂O₃ and Y₂O₃. It is determined that the Mg concentration ranges in vicinity of 0.15 at.% Mg to produce Mg:YAG ceramics of higher transparency.